Effects of Increasing Temperature on Bacterial Community Diversity in Mixed Stands of Artemisia argyi and Solidago canadensis in Eastern China - Haochen Yu; Guangqian Ren; Zhiyun Huang; Shanshan Qi; Biying Zhao; Xue Fan; Zhaoqi Zhu; Zhicong Dai; Daolin Du (Microorganisms)
Global climate change and invasive plants significantly impact biodiversity and ecosystem functions. This study focuses on the effects of progressive warming on microbial communities within the Solidago canadensis invasion community, simulated through six stages of invasion progression, from minimal to dominant S. canadensis presence alongside native Artemisia argyi, in bulk soils collected from a natural habitat and cultivated under controlled greenhouse conditions. Utilizing high-throughput sequencing and microbial community analysis on 72 samples collected from the S. canadensis invasion community, the shifts in soil microbiota under varying warming scenarios were investigated (+0 °C, +1.15 °C and +1.86 °C). We observed significant shifts in invasion community soil bacteria in response to warming, with Acidobacteria, Actinobacteria, and others showing distinct responses between baseline and warmed conditions, while groups like Chlorobi and Cyanobacteria only differed significantly at higher temperature extremes. The random forests algorithm identified 14 taxa as biomarkers and a model was established to correlate S. canadensis invasion community soil microbiota with progressive warming. Co-occurrence network analysis revealed that moderate warming enhances microbial connectivity and the presence of a super-generalist, ASV 1160. However, further warming disrupts these networks by eliminating key generalists, revealing a potential reduction in network stability and diversity. These findings illuminate the dynamic responses of microbes in S. canadensis invasion community soil to varying temperature regimes, suggesting a model for successional dynamics and offering a deeper comprehension of microbial community shifts amid climatic fluctuations. This study delineates how warming significantly reshapes the soil microbial composition, potentially impacting S. canadensis’s invasion success unfavorably, thereby highlighting the importance of considering microbial dynamics in ecological management.